Boutique Hotel in Badung-Bali District Application of Luxurious Concepts in Exclusive Type Room Interiors - Santhi, Komang Savitri Pratishita; Siwalatri, Ni Ketut Ayu; Wiryawan, I Wayan (Journal of A Sustainable Global South, 2018)
As the time passes by, people's lifestyles and tourism in Bali have developed rapidly. Business people have made ho-tels the main target in tourism because it means to providing services includes hotel, hostel or  motel. Therefore this fa-cility is very important for developed of tourism in Bali. The ambience and concepts that are owned by the hotels, espe-cially in the rooms, are very influential to increase the number of tourists who wish to stay at the hotels, both from the in-terior   design and atmosphere that is served and able to make tourists feel comfortable. Luxurious hotel is one of the hotels that has been loved by many people today and has developed throughout the hospitality industries, especially 5 stars   standard  hotels. Interior design with luxury concept has characteristics that can be seen from using materials of good quality and aesthetic value which are more than the value of its function. The application of this luxurious concept in the interior of hotel rooms such as several parts in the form of upper elements that use ceiling and hanging lamps and walls that use wooden partitions arranged vertically and use of materials with gold and neutral colors such as brown and white on most interior elements in the boutique hotel room. With the application of the luxurious concept, can create the ambience of the space become more elegant. Index Terms — luxury,boutique,hotel,interior.